The archaeology of Anatolia. - Steadman, Sharon R.; McMahon, John Gregory, 1953- (The Archaeology of Anatolia: Recent Discoveries., 2015)
This volume brings together the latest reports on archaeological projects, including excavation and survey, from all periods and every region of Anatolia.